Visions, prophecies, madness: The textual and pictorial approaches of William Blake and Josef Váchal - Dvořák, Josef (Univerzita Pardubice, 2007)
The aim of this thesis is to respond to a conclusion proposed by the lay public suggesting the similitude between the works and lives of the British poet and engraver William Blake and the Czech writer and versatile artist Josef Váchal. Despite the span of nearly one century which separates the two artists, the backgrounds of their livesoffer a number of analogies providing explanations for characteristic parallels between their artistic productions. Besides, special attention is given to map all most explicit influences which made both artists strive for a linkage of textual and pictorial elements into one compact unit: the book. In case of William Blake, this concerns his unique interpretation of illuminated books from the early stage of his production, which is connected to Blake's revolutionary invention of relief etching. As far as Váchal is concerned, the subject of this study becomes the artist's attempt to reproduce a beautiful book, characteristic especially of his early works. This thesis tries to verify particular similarities and differences of social impacts on forming the artists' conception of their book production.
Vidění, proroctví, šílenství: Textové a obrazové přístupy Williama Blakea a Josefa Váchala
Keywords: similitude; books production; textual elements; pictorial elements; analyses; William Blake; Josef Váchal; podobnost; knižní díla; textové složky; obrazové složky; analýzy